PENGARUH PENDEKATAN SAINTIFIK DAN GAYA BELAJAR TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAMDI MADRASAH TSANAWIYAH MESRAKOTA PEMATANGSIANTAR - Mul Iadi (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The purpose of this study was to find out: (1) differences in AkidahAkhlak learning outcomes of students taught with scientific approacheswith students taught with contextual approaches, (2) differences inlearning outcomes Akidah Akhlak students who have visual, auditory andkinesthetic learning styles, and (3) the influence of the scientific approachand student learning styles on the learning outcomes of Akidah Akhlak.This research method is quasi-experimental with the population of thisstudy are students of class VII (Seven). The sample was chosen into twoclasses with cluster random sampling technique, in this case selected forthe experimental class with a scientific approach is class VIIa with thenumber of students 31, while for the control class that is the contextualapproach is class VIId with the number of students 34. Instruments of datacollection is a questionnaire and test of learning outcomes. The techniqueby analysis of variance (Anava) at